Transient ascending ST‐segment depression and widening of the S wave in 3‐channel Holter monitoring—A sign of dromotropic disturbance in the right ventricular outflow tract in the Brugada syndrome: A report of five cases. Issue 2 (9th December 2021) - de Andrade, Antonio Thomaz; Barbosa‐Barros, Raimundo; Nikus, Kjell; Raimundo, Rodrigo D.; de Abreu, Luiz C.; Sacilotto, Luciana; Darriuex, Francisco C. C.; Yanowitz, Frank G.; Brugada, Pedro; Pérez‐Riera, Andrés Ricardo
Abstract: Background: Brugada syndrome (BrS) is somewhat a challenging diagnosis, due to its dynamic pattern. One of the aspects of this disease is a significant conduction disorder located in the right ventricular outflow tract (RVOT), which can be explained as a consequence of low expression of Connexin‐43. This decreased conduction speed is responsible for the typical electrocardiographic pattern. Opposite leads located preferably in inferior leads of the electrocardiogram may show a deep and widened S wave associated with ascending ST segment depression. Holter monitoring electrocardiographic (ECG) aspects is still a new frontier of knowledge in BrS, especially in intermittent clinical presentations. Methods: We describe, as an exploratory analysis, five case series of intermittent type 1 BrS to demonstrate the appearance of ascending ST segment depression and widening of the S wave, during 3‐channel 24h‐Holter monitoring (C1, C2 and C3) with bipolar leads. Results: In the five cases described, the ST segment depression was observed mainly in C2, but in some cases also in C1 and C3. Only case 1 presented concomitant intermittent elevation of the ST segment in C1. All cases were intermittent. Conclusion: The recognition of an ECG pattern with ascending ST‐segment depression and widening of the S wave in 3‐channel Holter described in this case series should raise a suspicion of the BrS and suggests the counterpart of a dromotropic disturbance registered in the RVOT and/or reciprocal changes.